2012
DOI: 10.1017/s1478951512000594
|View full text |Cite
|
Sign up to set email alerts
|

Care for the cancer caregiver: A systematic review

Abstract: Objective Informal caregivers (ICs) are relatives, friends, and partners who have a significant relationship with and provide assistance (i.e., physical, emotional) to a patient with a life-threatening, incurable illness. The multidimensional burden that results from providing care to a patient with cancer is well documented, and as a result, a growing number of psychosocial interventions have been developed specifically to address this burden. The purpose of the present study was to characterize the state of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
242
0
14

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(261 citation statements)
references
References 145 publications
5
242
0
14
Order By: Relevance
“…Research on interventions for family caregivers has shown that existential therapy focusing on the development of hope (30) and home care services (31) is effective in supporting caregivers of care recipients who have advanced cancer and palliative care needs. The findings of a previous study on communication skills training for spousal caregivers of breast cancer patients (32) suggest that such training may be a useful means of support for male caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…Research on interventions for family caregivers has shown that existential therapy focusing on the development of hope (30) and home care services (31) is effective in supporting caregivers of care recipients who have advanced cancer and palliative care needs. The findings of a previous study on communication skills training for spousal caregivers of breast cancer patients (32) suggest that such training may be a useful means of support for male caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…Even though much has been done concerning patient empowerment, more attention is needed on the effects and support of telemedicine on family caregivers and on how promising e-health programmes are in responding to their needs [39,40]. Despite caregivers' requests for provision of support and information competence, a recent meta-review on the effects of eHealth for patients and informal caregivers confronted with cancer concludes that there is a paucity of systematic reviews on this topic and that web-based interventions focused on family members are still an unexplored area [41].…”
Section: Introductionmentioning
confidence: 99%
“…[8][9] Systematic reviews also indicated that supportive care interventions improved cancer caregivers' psychological status, emotion, well-being, disease related knowledge, quality of life, and coping strategy. 10 However, the traditional modes of delivering interventions have a major disadvantage of poor accessibility. For example, some parents may be less motivated to attend intervention training courses or unable to find substitute caregiver for their children to allow them to attend the training.…”
Section: Introductionmentioning
confidence: 99%
“…For example, some parents may be less motivated to attend intervention training courses or unable to find substitute caregiver for their children to allow them to attend the training. 10 Mobile Health (mHealth) is an emerging technology to make supportive care more accessible for parents of children with ALL. mHealth interventions can be used to the manage side effects, improve drug adherence, provide cancer care information, plan and follow up care, and detect and diagnose cancer.…”
Section: Introductionmentioning
confidence: 99%